Infant and child mortality in India: levels, trends and determinants - National Institute of Medical Statistics (NIMS); Indian Council of Medical Research (ICMR); United Nations Children's Fund (UNICEF) (New Delhi: National Institute of Medical Statistics, 2012)
Post-neonatal mortality rate (deaths after 28 days of life but before one year) is as high as 49% in case of a child born to an illiterate mother as against just 8% to a mother with 12 years of formal education. The IMR is 110% in case of an illiterate mother against 28% in case of those with education. A child born to a mother with 11 years of formal education has been found to be 60% less likely to die in the first month of birth. However, this goes down to 20% in case of a child born to a mother with eight years of education. A first-of-its-kind government study called "Infant and Child Mortality in India - Levels Trends and Determinants" prepared by the National Institute of Medical Statistics, which is part of the Indian Council of Medical Research ICMR), says that between 1981 and 2005, IMR among children born to illiterate mothers has been consistently higher than those born to mothers with any education. The report says, numerous arguments support a causal relationship between mother's education and under-five mortality. Education generally acts to reduce under-five mortality levels. A mother's education is important because it facilitates her integration into a society impacted by traditional customs, exposes her to information about better nutrition, use of contraceptives to space births and knowledge about childhood illnesses and treatment.
Introduction -- Data and Methodology -- Levels and trends of Under-Five Mortality and its Components -- Effects of Socio-Economic Characteristics on Components of Under-Five Mortality -- Effects of Maternal and Demographic Characteristics on Components of Under-Five Mortality -- Effect of Environmental Factors on Components of Under-Five Mortality -- Inequalities in Child Survival in India and its States -- Summary and Conclusions -- Reference -- Annexures.
Keywords: Infant Mortality; India; Children; Child Health; Education; Health Effects; Environment; Women; Children--Mortality; Infants--Mortality